2012
DOI: 10.1097/won.0b013e31823efd47
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence Features, Risk Factors, and Quality of Life in Turkish Women Presenting at the Hospital for Urinary Incontinence

Abstract: Urinary incontinence exerts a major influence on health-related quality of life in affected women. Mixed UI was associated with the greatest level of social embarrassment assessed by the I-QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Similarly, Basak et al. () reported that UI moderately affects the quality of life in Turkish women. Yagmur & Ulukoca (), Isikli et al.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Similarly, Basak et al. () reported that UI moderately affects the quality of life in Turkish women. Yagmur & Ulukoca (), Isikli et al.…”
Section: Resultsmentioning
confidence: 87%
“…Despite evidence that UI is a clinically relevant problem that negatively impacts quality of life, the proportion of women who seek medical help is low in Turkey (Basak et al. ; Kok et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies in Western countries have assessed the risk factors and incidence of LUTS, there is a lack of epidemiological studies on the issue in Turkey. Such a study is of even greater importance because of the high delivery rate and urinary incontinence prevalence parameters in Turkey …”
Section: Introductionmentioning
confidence: 67%
“…Most of these studies report on the prevalence of urinary incontinence in Turkey, and there is a need for epidemiological studies specific to LUTS in women aged 40 and over . An understanding of the prevalence and risk factors of LUTS in women aged 40 and over may help to target treatment resources and take preventive steps in the future.…”
Section: Introductionmentioning
confidence: 99%